1990
DOI: 10.1002/sia.740160163
|View full text |Cite
|
Sign up to set email alerts
|

An XPS study of the initial stages of oxidation of hafnium

Abstract: The oxidation kinetics of polycrystalline hafnium (Hf) at room temperature a d low oxygen pressure (Poz -lo-' Ton) has been studied by x-ray photoelectron spectroscopy (XPS). After a chemisorption stage for exposures < 5 L, Hf suboxides are initially formed and are dominant until -25 L. HfO, appears at -10 L. Above 25 L, HfO, grows by oxidation of the suboxides, whereas the oxide film thickness remains constant. Above 500 L, a saturation region is obse~ed that corresponds to an oxide layer of 12 hi thick with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 16 publications
9
70
0
Order By: Relevance
“…The 1.19 and 3.94 eV chemical shifts for the suboxide and the full oxide are in qualitative agreement with the previously reported XPS values of 0.90 and 3.64 eV respectively. 4 Similarly, the chemical shift in the binding energy of the Hf 5p 3/2 level is determined as 3.9 eV exactly the same ͑within our experimental uncertainty͒ as the 4 f 7/2 shift. Figure 2 presents the spectra of hafnium foil in the presence of the native oxide at different photon energies in the range of 70-130 eV.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The 1.19 and 3.94 eV chemical shifts for the suboxide and the full oxide are in qualitative agreement with the previously reported XPS values of 0.90 and 3.64 eV respectively. 4 Similarly, the chemical shift in the binding energy of the Hf 5p 3/2 level is determined as 3.9 eV exactly the same ͑within our experimental uncertainty͒ as the 4 f 7/2 shift. Figure 2 presents the spectra of hafnium foil in the presence of the native oxide at different photon energies in the range of 70-130 eV.…”
Section: Resultssupporting
confidence: 77%
“…3 Morant et al were the first to report on a systematic XPS investigation of the initial stages of oxidation of hafnium. 4 They studied the oxidation kinetics of polycrystalline hafnium at room temperature under low oxygen pressures (ϳ10 Ϫ7 Torr) and reported that suboxides are formed in the early stages, and that HfO 2 formation proceeded through oxidation of suboxides. The film thickness saturates to a value of 12 Å ͑under their conditions͒ with an average Hf:O stoichiometry of 1:1.8.…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy of Hf 4 f 7/2 is measured to be 17.9 eV, in agreement with the range of values given in the literature ͑16.7-18.1͒. 12,13 In order to account for the different extents of charging in thicker HfO 2 samples, the Hf 4 f levels of known position are used as reference peaks, as they are sharp. In the case of ϳ15 Å SiO 2 /Si(100), we took advantage of the constant separation in energy between the Si 2p core level and the valence-band maximum.…”
supporting
confidence: 85%
“…The intensities [12] c Although one set of spin-orbit split peaks has been used to fit the Hf and Si suboxide components, normally, multiple peaks corresponding to Hf (1 -3)+ and Si (1 -3)+ are used with a range of BE. [1,10] of both oxide peaks change in the same way as the take-off angle is varied, confirming that they belong to the same phase. Previous work in (HfO 2 ) x (SiO 2 ) 1−x films has shown that as x increases, the Si 2p BE decreases and is always lower than in SiO 2 , whereas the Hf 4f BE increases and is always higher than in HfO 2 .…”
Section: Resultsmentioning
confidence: 53%
“…All spectra were fitted by comparing the binding energies of the component peaks to those of standards collected here or elsewhere (Table 1). [1,10] Because HfSi 0.5 As 1.5 is metallic, the Hf 4f component peak was fitted with an asymmetric lineshape, which arises from final-state effects as first described by Doniach andŠunjić. [11] In the clean surface, the spectra reveal some suboxides of Hf and Si that were formed from reaction with residual gases in the vacuum chamber.…”
Section: Resultsmentioning
confidence: 99%